(untitled) - Ernest E Thompson (San Diego, California, 1996)
The book describes and illustrates with detailed drawings general animal features such as hair, skin folds, nerves, glands, ligaments, and tendons. It then discusses general principles by a comprehensive study of the dog, and continues with other species such as the horse, giraffe, buffalo, lion, sparrow, and peacock